Expression of genes related with the rna-directed dna methylation (rddm) pathway in Eragrostis curvula sexual and apomictic genotypes - Selva, Juan Pablo (2014)
Apomixis in plants refers to a diverse group of developmental behaviors resulting in asexual reproduction through seeds. Apomictic individuals bypass both meiotic reduction and egg cell fertilization to produce offspring that are exact genetic replicas of the maternal plant. Given the established relationships between sexual and apomictic pathways, different models have been proposed to explain the occurrence of apomixis at the molecular level involving genetic and epigenetic mechanisms. Weeping lovegrass [Eragrostis curvula (Schrader) Nees] is an apomictic perennial grass native of Southern Africa. The type of apomixis present in the E. curvula is pseudogamous diplospory. There are recent evidences on the role played by certain proteins of the RdDM pathways involved in gametophytic apomixis expression, suggesting an epigenetic regulation of the trait. It was reported in maize that loss-of-function of the dmt103 and dmt102 methyltransferases genes partially mimics apomictic developments. Similarly, loss-of-function in ago104, a maize homolog of ago9, also results in apomixis-like traits, giving rise to up to 70% of functional unreduced female gametes. These data suggest that an epigenetic regulation plays a role on the establishment of apomixis. In this work we studied the expression of EcDmt102-like and EcAgo104-like genes associated to the RdDM pathway in flowers and leaves of sexual and apomictic E. curvula plants. Using RNA seq data was possible to obtain the complete cDNA sequence for both genes from both apomictic and sexual genotypes. The phylogenetic analysis indicated that these genes group together in the same clade with the corresponding ones of Arabidopsis and Zea mays. The EcDmt102-like and EcAgo104-like genes profiles were analyzed using qRT-PCR in leaves and different stages of reproductive tissue. The expression profile obtained for EcDmt102-like was relatively higher in reproductive tissue of sexual plants, being down-regulated in apomictic ones. Expression of this gene was not observed in leaves from both genotypes. The expression pattern of EcAgo104-like was complex and is still under study because occurrence of a putative alternative splicing in the apomictic genotypes is being analysed. Our results support the reported roles played by this genes in gametophytic apomixis in other plant species.